Kegiatan kokurikuler mendukung pendalaman materi siswa di SMA Negeri 1 Jakenan - Amida, Ale Sandya Rindi; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
Co-curricular activities are activities carried out outside curricular and extracurricular hours. This study aims to find out that co-curricular activities support the deepening of student material. The method used in this study is a qualitative method of experimentation. In this study, data collection used field experiments. As for data management using content analysis. In this study, the author found four co-curricular activities that can support the deepening of student material, namely MOPDB (New Student Orientation Period), GLS (School Literacy Movement), Adiwiyata School, and Study Tour. These activities have been proven to support the deepening of student material inside and outside the student subject matter and foster good character for students.